2016
DOI: 10.1016/j.molcel.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The Flexible Ends of CENP-A Nucleosome Are Required for Mitotic Fidelity

Abstract: CENP-A is a histone variant, which replaces histone H3 at centromeres and confers unique properties to centromeric chromatin. The crystal structure of CENP-A nucleosome suggests flexible nucleosomal DNA ends, but their dynamics in solution remains elusive and their implication in centromere function is unknown. Using electron cryo-microscopy, we determined the dynamic solution properties of the CENP-A nucleosome. Our biochemical, proteomic, and genetic data reveal that higher flexibility of DNA ends impairs hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 40 publications
19
75
0
Order By: Relevance
“…We employed a well-established approach for nucleosomes424344, recently extended to CENP-A nucleosomes assembled with a synthetic positioning sequence45 that employs hydroxyl radical-mediated cleavage of DNA. We used the same natural CENP-A nucleosome-positioning sequence from human centromeres1146 used in our HXMS experiments, but where it is end-labelled20 for hydroxyl radical footprinting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We employed a well-established approach for nucleosomes424344, recently extended to CENP-A nucleosomes assembled with a synthetic positioning sequence45 that employs hydroxyl radical-mediated cleavage of DNA. We used the same natural CENP-A nucleosome-positioning sequence from human centromeres1146 used in our HXMS experiments, but where it is end-labelled20 for hydroxyl radical footprinting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that the centromeric H3 variant CENP-A might not need histone H1 to interact with the linker DNA, as CENP-A contains a conserved domain that shows highly similarity with motifs present on the H1 tails. The results of the recent study by Roulland et al confirms these suggestions as they show a low binding affinity between CENP-A and H1 as a result of the flexible histone tails of CENP-A (Roulland et al, 2016). …”
Section: Mitotic Bookmarking and Epigenetic Memorymentioning
confidence: 61%
“…A recent study by Roulland et al showed the importance of the flexible tails of CENP-A in mitosis. When the flexible tail of CENP-A is switched with the more rigid tail of the canonical H3, several kinetochore proteins dislocate and severe mitotic and cytokinetic defects like aneuploidy are observed (Roulland et al, 2016). Although DNA sequences in centromeres have been shown not to be conserved, the centromeric H3 histone variant shows high levels of similarity across species (Cheeseman et al, 2004).…”
Section: Mitotic Bookmarking and Epigenetic Memorymentioning
confidence: 99%
“…The incorporation of different species of histone variants into nucleosomes provides further differentiation and epigenetic chromatin diversity [1, 8]. The differentiation and specific functions of chromatin directed by a histone variant is especially conspicuous at centromeres, where the H3 variant, CENP-A, is assembled into specialized nucleosomes that form the foundation for the kinetochore assembly [911]. The crystal structure of CENP-A revealed that it is quite similar to the structure of histone H3 variants and consists of an unstructured amino terminal αN-helix, α1 helix, Loop1, β1-sheet, β2-sheet, α2 helix, and α3-helix [12].…”
Section: Introductionmentioning
confidence: 99%
“…A domain found in the HFD of CENP-A, called the CENP-A targeting domain (CATD), mediates the specific interaction of CENP-A with HJURP and to date is the only domain identified essential for CENP-A centromeric localization [28]. Some modifications in the amino-terminus of CENP-A have recently been identified as regulatory signals for its centromeric targeting and chromosome segregation [9, 13, 29, 30]. However, the role of the amino-terminus of CENP-A is poorly understood.…”
Section: Introductionmentioning
confidence: 99%